Emotional fatigue in university students in times of COVID-19: psychometric properties - Desposorio Celis, Tania Gissela (2023)
Background: This research is based on the theoretical postulate of Maslach, established in her Burnout theory (Maslach & Jackson, 1982), focusing on the main dimension, emotional exhaustion, (Ramos et al., 2005), shifting from the work context to the university context. Objective: To determine the psychometric properties of the Emotional Exhaustion Scale in university students in the city of Trujillo. Method: A quantitative and instrumental design was used. A pilot test was conducted with 50 students, and a total sample of 307 subjects of both sexes, from public and private universities, aged between 18 to 30 years, was considered. Evidence of validity based on content and internal structure was analyzed. Results: The results of the confirmatory factor analysis show a unifactorial structure of 10 items with adequate fit indices (χ2/gl= 2.304; SRMR= .379; RMSEA= .065; CFI= .967; TLI= .957; and PCFI= .752). Furthermore, evidence of validity based on the relationship with other variables was obtained, using the Perceived Self-efficacy Scale in Academic Situations (EAPESA). Conclusion: A small inverse correlation was demonstrated In addition, the reliability by internal consistency of McDonald’s Omega was determined, with a value of .89, considered as acceptable. The scale presents adequate psychometric properties regarding the proposed model. Authorship contribution The authors participated in the entire development of the article.